Towards a Theory of the Anxiety of Ontology : differentiated working strategies, dramaturgical manipulations and the theme of death in the work of Marina Carr and Emma Dante - Donohue, Brenda (Trinity College (Dublin, Ireland). Italian Department, 2013)
This thesis provides a feminist and comparative analysis of the unique ontological position of two contemporary female playwrights, Marina Carr and Emma Dante, in the Republic of Ireland and Italy. It interrogates the specificity of their position within a profession that has traditionally been defined in masculine terms, and examines the influence of such a status on their artistic processes as well as their theatrical work. I propose a hypothesis that claims such an influence is manifest within the artists, and their work, in what I term (after Harold Bloom and Gilbert & Gubar) the Anxiety of Ontology. The thesis examines how a background of gender inequality alters the playwrights’ work, inspiring them to contest traditional forms and models and propose new feminine exemplars in their work. Harold Bloom’s Anxiety of Influence and Gilbert & Gubar’s Anxiety of Authorship inform my development of the theory of the Anxiety of Ontology, while Judith Butler’s notion of gender as a performative act assist my reading of the ontology of female playwrights as culturally separate and distinct from that of male playwrights and writers of novels, poetry and prose. The project is divided into six distinct sections, beginning with an introductory section, which situates the work of the two contemporary playwrights within the cultural and historical context of Italian and Irish theatre, as well as an overview of the situation of women playwrights internationally. Chapter Two examines in detail the working strategies that women playwrights employ in response to gender discrimination and as a manifestation of the Anxiety of Ontology. In response, the playwrights alter their working processes, which are analysed under four separate headings. Chapter Three identifies the manifold ways in which the Anxiety of Ontology may become manifest in the artistic offerings of the playwrights. It considers how Carr and Dante employ both theatrical form and content as sites of contestation and disruption, in an expression of their dissatisfaction with traditional theatre’s suitability for their own purposes, which vary from those of male writers. Chapter Four moves towards a consideration of the theme of death in the plays of Dante and Carr as a multiple signifier. In its scrutiny of the suicides of female protagonists in Carr’s and Dante’s plays, this chapter proposes the concept of “resistant suicide” as a reading through which some represented self-deaths could be seen as a moment of agency, authority and resistance on their behalf. Chapter Five continues this analysis in its contention that the same deaths can be read as mirrors for the playwrights’ own anxieties regarding the precarious and unstable nature of their artistic and professional position. In killing off their suicidal characters, specifically their female protagonists, Carr and Dante engage in a process with transformative and liberatory potential that attempts to kill off the author’s own Anxiety of Ontology. Finally, Chapter Six summarizes the links between the playwrights’ works, working strategies and the anxiety. It concludes with a look ahead and a consideration of what the future might hold for women writers for theatre.
Keywords: Language, Literatures & Cultural Studies, Ph.D.; Ph.D. Trinity College Dublin